COVID-19 and Living Donor Kidney Transplantation in Naples during the Pandemic. (15th October 2020) - Peluso, Gaia; Campanile, Silvia; Scotti, Alessandro; Tammaro, Vincenzo; Jamshidi, Akbar; Pelosio, Luigi; Caggiano, Marcello; Pagano, Teresa; Cuozzo, Francesco; D'Ambrosio, Fabrizio; Calogero, Armando; Dodaro, Concetta; et al.
Abstract : Introduction . SARS-CoV-2 is a virus that causes a potentially deadly syndrome that affects especially the respiratory tract. Kidney-transplanted patients are immunosuppressed and more susceptible to viral infections. We have examined our transplantation activity to explore the future role of kidney transplantation from deceased and living donors in COVID-19 era. Patients and Methods . The activity of our transplant center of Naples (one of the two transplant centers in Campania, South Italy) continued during the COVID-19 pandemic. We have analysed the kidney transplants carried out between March 9 and June 9, 2020, comparing these data with the numbers of procedures performed in the two previous years. Moreover, we have considered the possibility of performing living donor transplants during a worldwide pandemic. Results . From March 9, 2020, when the Italian lockdown begun, till June 9, 2020, five kidney transplants have been performed at our transplant center in Naples, all from deceased donors. The donors and the recipients have been screened for COVID-19 infection, and the patients, all asymptomatic, followed strict preventive measures and were fully informed about the risks of surgery and immunosuppression during a pandemic. All the transplanted patients remained COVID negative during the follow-up. The number of transplants performed has been constant compared to the same months of 2018 and 2019. In agreement with the patients, we decided to postpone living donor transplants to a period of greater control of the SARS-CoV-2 spread in Italy. Conclusion . Deceased donor kidney transplantation should continue, especially in a region with moderate risk, like Campania, with a more careful selection of donors and recipients, preferring standard donors and recipients without severe comorbidities. Living donor transplantation program, instead, should be postponed to a period of greater control of the SARS-CoV-2 spread, as it is an elective surgery and its delay does not determine additional risks for patients.